The Cambridge handbook of copyright limitations and exceptions - Balganesh, Shyamkrishna ca. 20./21. Jh; Sun, Haochen; Ng-Loy, Wee Loon 1965- (Cambridge University Press, 2021)
While copyright law is ordinarily thought to consist primarily of exclusive rights, the regime's various exemptions and immunities from liability for copyright infringement form an integral part of its functioning, and serve to balance copyright's grant of a private benefit to authors/creators with the broader public interest. With contributors from all over the world, this handbook offers a systematic, thorough study of copyright limitations and exceptions adopted in major jurisdictions, including the United States, the European Union, and China. In addition to providing justifications for these limitations, the chapters compare differences and similarities that exist in major jurisdictions and offer suggestions about how to improve the enforcement of copyright limitations domestically and globally. This work should appeal to scholars, policymakers, attorneys, teachers, judges, and students with an interest in the theories, policies, and doctrines of copyright law
Keywords: Copyright